Particleboards from Recycled Pallets - Ján Iždinský (MDPI AG, 2021)
Worldwide production of wooden pallets continually increases, and therefore in future higher number of damaged pallets need to be recycled. One way to conveniently recycle pallets is their use for the production of particleboards (PBs). The 3-layer PBs, bonded with urea-formaldehyde (UF) resin, were prepared in laboratory conditions using particles from fresh spruce logs (FSL) and recycled spruce pallets (RSP) in mutual weight ratios of 100:0, 80:20, 50:50 and 0:100. Particles from RSP did not affect the moisture properties of PBs, i.e., the thickness swelling (TS) and water absorption (WA). The mechanical properties of PBs based on particles from RSP significantly worsened: the modulus of rupture (MOR) in bending from 14.6 MPa up to 10 MPa, the modulus of elasticity (MOE) in bending from 2616 MPa up to 2012 MPa, and the internal bond (IB) from 0.79 MPa up to 0.61 MPa. Particles from RSP had only a slight negative effect on the decay resistance of PBs to the brown-rot fungus Serpula lacrymans, while their presence in surfaces of PBs did not affect the growth activity of moulds at all.